Induced expression of CCL19 promotes the anti-tumor ability of CAR-T cells by increasing their infiltration ability - Hu, Jian-fei; Wang, Zu-wei; Liao, Cheng-yu; Chen, Zhi-wen; Kang, Feng-ping; Lin, Cai-feng; Lin, Tian-sheng; Huang, Long; Tian, Yi-feng; Chen, Shi (Frontiers in Immunology, 2022)
Background: Chimeric antigen receptor-engineered T cell (CAR-T) therapy has shown promising potential for anti-cancer treatment. However, for pancreatic ductal adenocarcinoma (PDAC), the lack of infiltrative ability of these CAR-T cells leads to sub-optimal treatment outcome. Methods: Chemokine (C-C motif) ligand 19 (CCL19), the expression of which is regulated by the nuclear factor of activated T cell pathway, was transfected into targeting mesothelin CAR-T cells (mesoCAR-N19) using NFAT regulating element. It was expressed in activated CAR-T cells by OKT3 or mesothelin+ tumor cells but not in inactive cells. The migratory ability of these CAR-T cells was then measured. Subsequently, functional identification of these CAR-T cells was performed in vivo. In addition, the tumor lytic activity and proliferation of the CAR-T cells were measured in vitro. The degree of CAR-T cell infiltration and distribution into the PDAC tumors was examined using the immunohistochemical staining of hCD3 and the detection of CAR gene copy number by quantitative PCR. Finally, the functional assessment of chemokine (C-C motif) receptor 7 knock-out was performed in the CAR-T cells. Results: Through in vitro Transwell assays, it was demonstrated that mesoCAR-N19 can be specifically expressed in CAR-T cells activated by tumor cells compared with conventional mesothelin CAR-T (mesoCAR) cells. We also observed that upregulating the expression of CCL19 can increase the recruitment of additional T cells. In vivo studies subsequently revealed that this highly specific recruitment of T cell infiltration is associated with enhanced tumor-suppressive activities downstream. Conclusion: Induced expression of CCL19 can promote the anti-tumor ability of CAR-T cells by increasing their infiltrative ability. This study potentially uncovered novel method of activating CAR-T cells to enhance their infiltrative capacities, which offers a novel direction for PDAC treatment.